(x^2yz)^2(xy^2z^2)/(xyz)^2

1 answer

To simplify the expression:

First, expand the terms inside the parentheses:

(x^2yz)^2 = x^4y^2z^2
(xy^2z^2) = xy^2z^2
(xyz)^2 = x^2y^2z^2

Next, substitute the expanded terms into the original expression:

(x^4y^2z^2 * xy^2z^2) / (x^2y^2z^2)

Now, multiply the terms:

(x^4 * x * y^2 * y^2 * z^2 * z^2) / (x^2 * y^2 * z^2)

Simplify the expression:

= x^5 * y^4 * z^4 / x^2 * y^2 * z^2

= x^(5-2) * y^(4-2) * z^(4-2)

= x^3 * y^2 * z^2

Therefore, the simplified expression is x^3y^2z^2.